IMPROVING SECONDARY STUDENTS’ READING COMPREHENSION THROUGH QUESTION-ANSWER-RELATIONSHIPS (QAR) STRATEGY - Eva Amelia; Jaya Nur Iman (FKIP Universitas Tridinanti, 2022)
This research aimed to improve students’ reading comprehension achievement using Question-Answer-Relationship (QAR) strategy and to determine students' perception toward the application of QAR strategy. The research design was a pre-experimental design. The population in this research was seven grade students of SMP Tri Dharma consisting of three classes, namely VII A, VII B, VII C. The researchers used 33 students of class VII B as the sample for this research. This research used reading test and a closed ended questionnaire to collect the data. This research used paired sample t-test and percentage analysis to analyze the obtained data. The results of paired sample t-test showed that t- obtained was 25.438 and p. was 0.000 (p<0.05). This means that there was a significant improvement in students' reading comprehension after being taught with the QAR strategy. The results of percentage analysis showed that the students' perception of the QAR strategy was positive. It perceived that the QAR strategy was effective to help the students improve their reading comprehension achievement significantly. Those findings indicated that the QAR strategy was effective in improving students' reading comprehension achievement of descriptive texts for the seventh graders of SMP Tri Dharma Palembang in the academic year 2021/2022.